(untitled) (Talenta Conference Series: Science and Technology (ST), 2018)
Cellulose from paper pulp was alkalized with NaOH 30%; then carboxymethylated with monochloroacetic acid producing carboxymethyl cellulose (CMC). CMC resins was subsequently alkalized again with NaOH 30% producing sodium carboxymethyl cellulose (Na-CMC) before esterification/amination reaction with epichlorohydrin/ethylendiamine. Esterification/amination reaction with epichlorohidrin/ethylendiamine was carried out in two steps as well. Na-CMC was reacted with epichlorohydrin, and in the second step, 2-oxiranylmethyl carboxymethyl cellulose was reacted with ethylendiamine producing cellulose-g-epichlorohydrin/ethylendiamine. FT-IR spectroscopy analysis indicated CN Amine vibration in the region 1417 cm-1 and in the 1600 cm-1 region attributed to vibration of C=O group. Morphological analysis using SEM showed homogeneous and porous at their structure.